Study of carbon transport in the scrape-off layer of HL-2A with impurity sources located at limiter, dome, and divertor. (25th August 2015) - Cui, Z.Y.; Morita, S.; Kobayashi, M.; Ding, X.T.; Ji, X.Q.; Cheng, J.; Dong, C.F.; Sun, P.; Zhang, K.; Zhou, H.Y.; Mao, R.; Nie, L.; et al.
Abstract: Impurity transport in the scrape-off layer (SOL) has been studied in ohmically heated discharges of the HL-2A tokamak based on space-resolved vacuum ultraviolet spectroscopy. The vertical profile (from the plasma center to the lower X-point) of carbon emissions of CIII (977 Å: 2s 2 1 S0 -2s2p ) and CIV (1548 Å: 2s 2 S-2p 2 P) as well as the ratio of CIV to CIII were measured to investigate the edge impurity transport with relation to impurity source locations and sputtering characteristics. The experimental result shows that the impurity profile in the SOL has been clearly changed against different source locations. The emission of CIII and CIV from the mid-plane is stronger than that from the X-point when the impurity source is located at the divertor plate. The profile becomes flat as a result. When the impurity source changes to the dome source, the profile clearly changes to a slightly peaked one, indicating the edge carbon emission at the X-point is stronger than the mid-plane. The change to the limiter source makes the profile further peaked by increasing the carbon emission at the X-point. In the case of the dome impurity source, the intensity of CIII/ n e and CIV/ n e, normalized to line-averaged electron density, n e, decreases with n e at low n e ( n e ⩽ 2.6 × 10 19 m −3 ) and becomes saturated at high n e ( n e > 2.6 × 10 19 m −3 ). In contrast, the ratio of CIV to CIII increases with n e at low n e and starts to decrease at high n e . A numerical simulation with 3D edge plasma transport code, EMC3-EIRENE, suggests that a poloidal asymmetry in the impurity flow profile and an enhanced physical sputtering play an important role in the edge impurity distribution, particularly in the screening efficiency of C 2+ and C 3+ ions in the SOL region of the HL-2A tokamak.